Methylmercury activates enhancer-of-split and Bearded complex genes independent of the Notch receptor. - Rand, M.D.; Bland, C.E.; Bond, J. (Toxicological Sciences, 2008)
Methylmercury (MeHg) is a persistent environmental toxin that has targeted effects on fetal neural development. Although a number of cytotoxic mechanisms of MeHg have been characterized in cultured cells, its mode of action in the developing nervous system in vivo is less clear. Studies of MeHg-affected rodent and human brains show disrupted cortical and cerebellar architecture suggestive of mechanisms that augment cell signaling pathways potentially affecting cell migration and proliferation. We previously identified the Notch receptor pathway, a highly conserved signaling mechanism fundamental for neural development, as a target for MeHg-induced signaling in Drosophila neural cell lines. Here we have expanded our use of the Drosophila model to resolve a broader spectrum of transcriptional changes resulting from MeHg exposure in vivo and in vitro. Several Notch target genes within the Enhancer-of-split (E(spl)C) and Bearded (BrdC) complexes are upregulated with MeHg exposure in the embryo and in cultured neural cells. However, the profile of MeHg-induced E(spl)C and BrdC gene expression differs significantly from that seen with activation of the Notch receptor. Targeted knockdown of Notch and of the downstream coactivator Suppressor of Hairless (Su(H)), shows no effect on MeHg-induced transcription, indicating a novel Notch-independent mechanism of action for MeHg. MeHg transcriptional activation is partially mimicked by iodoacetamide but not by N-ethylmaleimide, two thiol-specific electrophiles, revealing a degree of specificity of cellular thiol targets in MeHg-induced transcriptional events.